Analysis of joint variation between human cases of tegumentary leishmaniasis and sand fly abundance in a hyper endemic area of Argentina - Almazán, María Cristina (2019)
Leishmaniases are a group of diseases caused by Leishmania parasites that are transmitted by sand fly female bite. In Argentina, the north of Salta province is a hyper-endemic area of Tegumentary Leishmaniasis (TL), being Oran department one of the most affected zones. To achieve deeper knowledge about the disease transmission in that region, we studied the joint variation of TL cases and sand fly abundance in two periurban sites of Oran. Sand fly captures were executed with CDC traps placed at the neighborhoods El Cedral (EC) (one night/sampling) and Taranto (TA) (three nights/sampling) across a year. Species identification of female sandflies was made by observation of spermatheca and cibarium. Also, the clinical information of patients diagnosed at Instituto de Investigaciones de Enfermedades Tropicales (IIET) since 1989 to 2018 was analyzed to determine the monthly mean of TL cases and the time of evolution of lesions. A total of 102 female sandflies were caught in EC neighborhood, while 1,434 in TA. The most abundant species was Nyssomyia neivai. The months with the highest proportion of gravid females were December and February for EC and TA neighborhoods, respectively (p<0.05). Regarding patient information, the male: female ratio was 6:1 with a median age of 32 years old. The time of evolution determined was one month. It was seen that the peak of patient cases took place in March for EC and in May for TA neighborhoods, namely three months later. This lag between gravidness period (high risk of infection) and peaks of TL cases may be explained due to the time of evolution (one month), plus an incubation period that seems to last two months. Considering the sex ratio and the productive age of patients, the transmission could have been mainly sylvatic during work activities. The analysis of joint variation allowed reaching a better characterization of disease transmission which is fundamental for designing and implementing prevention and control measures.